Reassessing our views of basic science towards revitalizing our basic research programs - Velasco, Luis Rey I. and Lit, Ireneo L. Jr (Asia Life Sciences : the Asian International Journal of Life Sciences, 2010)
Concepts, definitions and views about basic science and research in relation to applied research and technology and the apparently changing trends in worldwide and local views are discussed. As in most treatises, the importance of basic research to national development is reaffirmed as well as the paradox that it remains less funded and prioritized compared to applied and technological research. However, we argue for reassessment of our views of basic research is and address this not only to the scientist sector but also to the policy-makers and funding agencies. Many times, the distinction between basic and applied research is vague and rather than delve on hair-splitting definitions, we argue for setting our aims higher towards theory generation and an increased international publication output, founded on honest-to goodness science and scientific culture.